Optimal Incorporation, Structure of Debt Contracts, and Limited-Recourse Project Financing - Chemmanur, Thomas J.; John, Kose (Journal of Financial Intermediation, 1996)
We analyze the interrelationships among the corporate organization structure, the capital structure, and the ownership structure of a firm with multiple projects, when incumbent management derives control benefits. The choices made by firm management are: (1) Whether to set up projects as a joint firm or as separate firms (spin-off), (2) the amount of debt financing to use, (3) the structure of the debt contract (e.g., straight debt on the joint firm, limited-recourse project financing, or spin-off with straight debt), and (4) the fraction of equity to hold in each firm (ownership structure). Differences in managerial ability across projects, benefits of control, and the probability of loss of control through a takeover or through bankruptcy are driving factors in this model. We relate the project characteristics to the optimality of spin-offs and limited-recourse project financing arrangements, and derive implications for the allocation of debt and the ownership structure across projects.Journal of Economic LiteratureClassification Numbers: G32, G34, D21.